2010
DOI: 10.3390/molecules15107292
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant-Prooxidant Properties of a New Organoselenium Compound Library

Abstract: The present study describes the biological evaluation of a library of 59 organo-selenium compounds as superoxide (O2─) generators and cytotoxic agents in human prostate cancer cells (PC-3) and in breast adenocarcinoma (MCF-7). In order to corroborate that the biological activity for selenium compounds depends on the chemical form, a broad structural variety is presented. These structures include selenocyanates, diselenides, selenoalkyl functional moieties and eight newly synthesized symmetrically substituted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 49 publications
1
57
0
3
Order By: Relevance
“…Moreover, many studies reported that 50-90% of consumed selenite was lost and excreted in urine due to the short retention time in the gastrointestinal tract (52)(53)(54). It has been also evidenced that high dose supplementation of selenite may cause various adverse effects due to its pro-oxidant property, which depends on the concentration and other factors (55). Additionally, there is an emerging concern with potential adverse side effects of long-term oral Se supplementation methods that includes possible increased risk of type-2 diabetes (29).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, many studies reported that 50-90% of consumed selenite was lost and excreted in urine due to the short retention time in the gastrointestinal tract (52)(53)(54). It has been also evidenced that high dose supplementation of selenite may cause various adverse effects due to its pro-oxidant property, which depends on the concentration and other factors (55). Additionally, there is an emerging concern with potential adverse side effects of long-term oral Se supplementation methods that includes possible increased risk of type-2 diabetes (29).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, organo-Se compounds modulate extracellular redox by induction of extracellular cysteine and cell-surface thioredoxin reductase (36). The administration of Se drugs may induce either oxidant or antioxidant effects in the cells (37)(38)(39) by oxidation or reduction of thiol-containing proteins, depending on the influence of neighboring groups and redox potential (31). Se is essential for antioxidant activity but may have pro-oxidant properties at higher concentrations.…”
mentioning
confidence: 99%
“…the substantial role of human selenoproteins in antioxidant defense system and cancer protection. [3,4] In all living cells, there exists a constant balance between the generation of reactive oxygen species (ROS) and their destruction via antioxidant defense mechanisms. [5,6] ROS, including superoxide radical anions, hydroxyl radicals and hydrogen peroxide, participate in a variety of normal biochemical functions, as well as in abnormal pathological processes causing the cellular damage.…”
Section: Introductionmentioning
confidence: 99%